Analisis Deformasi di Lampung dan Selat Sunda Berdasarkan Data GNSS tahun 2018 hingga 2021 - Anggara, Ongky; Rahadianto, Muhammad Ario Eko; Alif, Satrio Muhammad; Isnaini, Een Lujainatul (Universitas Andalas, 2024)
The Lampung Province and Sunda Strait have a seismic gap zone with the potential for major earthquakes in the future. This study analyzes the deformation occurring in this region using continuous Global Navigation Satellite System (GNSS) station data from Indonesia Continuously Operating Reference Station (InaCORS) and Sumatran GPS Array (SuGAr) from 2018 to 2021.5. The GNSS data was processed using the Bernese 5.2 scientific software, applying least squares for velocity changes and statistical tests to analyze significance. The data processing was carried out in two schemes: the first scheme covering 2018-2020, and the second covering 2019-2021. The results of the deformation analysis from 2018 to 2021, using two continuous GNSS data processing schemes, showed velocity changes relative to the Sundaland Plate ranging from 2 mm/year to 20 mm/year. In the eastern region of the Sumatra fault, the velocity changes were smaller, around 5 mm/year, due to the minimal influence of tectonic activity. However, in the Sunda Strait region, the deformation was influenced by volcanic activity. The deformation occurring in Lampung Province and the Sunda Strait, based on GNSS velocity changes, significantly contributes to tectonic and volcanic activities.